2007 December - ECOWAS (ECOWAS, 2007)
ECONOMIC COMMUNITY OF WEST AFRICAN STATES FIFTY-NINTH SESSION OF THE COUNCIL OF MINISTERS, OUAGADOUGOU, 14-15 DECEMBER 2007
Council of Ministers 14-15 December 2007
Keywords: Council of Ministers 14-15 December 2007